Expressions of toll-like receptors and cytokine modulation of antiviral innate immune responses in feline infectious peritonitis virus infection - Megat Mazhar Khair, Megat Hamzah (2020)
Feline infectious peritonitis (FIP) is a fatal immune-mediated disease of domestic cats caused by feline infectious peritonitis virus (FIPV), a member of coronavirus family. Previous studies have shown that the lack or absence of adaptive cellular immunity and aberrant antibody production may lead to cats succumbing to FIP. FIPV viral protein has been shown to antagonize the production of type I interferon (IFN), the key cytokine crucial during early stage of viral infection and downregulate the production of anti-inflammatory cytokine such as IL-10. Natural killer (NK) cells, another important innate immune cell has been shown to be dysregulated in FIPV infection, suggesting the importance of innate immunity in FIP pathogenesis. Despite these findings, the information on pattern recognition receptors (PRRs) that play a role in the detection of common molecules on pathogens, or also known as pathogen-associated molecular patterns (PAMPs) is still lacking. Therefore, this study attempts to investigate the role of the Toll-like receptors (TLRs), one of the PRRs in FIPV infection in vitro and ex vivo. Stimulation of TLR pathway activates the NF-κB and type I IFN-related pathways which in turn produce pro-inflammatory cytokines such as TNF-α, and type-I IFN (IFN- α, IFN-β). To achieve these objectives, Crandell-Rees Feline Kidney (CRFK) cells and feline CD14+ monocytes were infected with FIPV 79- 1146 and harvested at 4, 12, and 24 hours post-infection (hpi). The infection of FIPV into these cells was confirmed by immunofluorescence (IF) assay. The mRNA expression of several TLRs (TLR3, TLR7, and TLR9) and some of downstream cytokines (TNF-α, IL-10, and IFN-β) were measured using real time PCR (qPCR). The results were then correlated with the viral load copy number. Results from the in vitro study revealed the involvement of TLR9 in TNF-α, and IFN-β cytokine modulation in CRFK cells. However, TLR3 was expressed at low level and remained stable throughout the in vitro infection while TLR7 was not detectable. In contrast, TLR7 expression was induced upon ex vivo infection of feline monocytes at earlier time point indicating the activation of TLR7 by binding to its ligand, single-stranded RNA. However, its expression was significantly reduced at later time points which could be due to the immune evasion strategy posed by FIPV. A similar trend was also observed for TNF-α expression postulating the role of TLR7 in the regulation of TNF-α which has been implicated as the major pro-inflammatory cytokine seen in FIP cats. Furthermore, IFN-β gene was also expressed throughout the course of infection which could be mediated by TLR7 activation and independent of TLR3 and TLR9 signaling pathways as the level of expression of these two TLRs remained stable. In general, the viral replication kinetics in CRFK cells and feline monocytes were consistent with other studies where the virus increased from 4 hpi to 12 hpi and maintained or reduced from 12 hpi to 24 hpi. Interestingly, the expression of TLR7 in monocytes of one seronegative cat was sustained throughout the infection, and the expression of TNF-α, IL-10, and IFN-β were markedly upregulated suggesting a control of viral protein synthesis by the immune system which was confirmed by the absence of viral antigen by IF, although the viral RNA was present. Taken together, this study provides a new insight on the role of TLRs in modulating the immune responses in FIPV infection. Although different cells express a different set of TLRs as observed in this study, this report implicates the role of TLR7 and TLR9 in FIPV infection, therefore setting up an avenue for further investigation into their signaling pathway and possible formulation of new therapeutic strategies.